Spatial and temporal analysis of population trade service in Kharkiv region for parameters of social and geographical system trajectory motion - Кобилін, П. О. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
The article deals with spatial and temporal features of population trade service of Kharkiv region. The study has been implemented from the point of view of the system approach to human geography and the definition “social and geographical system” has been given. For the qualitative human-geographical analysis the parameters of social and geographical system trajectory have been selected. They include: cosine of an angle between social and geographical system trajectory and optimal trajectory; distance traveled by social and geographical system in multidimensional feature space (L); distance between the current point and the minimal development point (coordinates beginning) (L0); distance from the current point to the maximum development point (end point) (L1); progress coefficient. Cosine of an angle between social and geographical system trajectory and optimal trajectory characterize trajectory motion direction, others – linear indicators. Districts distribution for these parameters showed that the most economically developed districts (Kharkivs'kyy, Krasnohrads'kyy, Derhachivs'kyy, Zmiyivs'kyy, Balaklis'kyy, etc.) are characterized by the greatest advancement in development (progress coefficient, distance between the current point and the minimal development point); the worst developed, farthest from the regional center – correspondingly, the worst advancement. The indicator of distance from the current point to the maximum development point is inversely proportional to the distance from the coordinates origin to the current point. In dynamics the trend for increasing the indicators during the studied period is observed in the economically developed districts, and decrease in motion intensity is observed in the worst developed districts. Among the towns of regional subordination the city of Kharkiv is highlighted.